1995
DOI: 10.1037/0022-0167.42.2.242
|View full text |Cite
|
Sign up to set email alerts
|

Self-talk of group therapists.

Abstract: To identify group leader cognitions and the role experience may play in leader cognitive schemas, 60 participants were placed in 1 of 3 groups on the basis of group-leading experience and were exposed to a 20-min videotape of a group session, during which they completed a thought-listing instrument. Two judges free sorted the 1,299 collected thoughts and identified and defined 17 distinct thought categories. Three trained judges then placed 1,271 (97.8%) of the thoughts into these categories. Differences among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
(36 reference statements)
1
21
0
Order By: Relevance
“…Stockton reported that these unique intentions were specifically related to group counseling and working with multiple clients. They also found that intention categories were similar to the already discussed self-talk categories of Hines, Stockton, and Morran (1995), which demonstrated that self-talk and intentions are closely related constructs. This provided strong support that self-talk is involved in the impact of intentions on actual intervention selection.…”
Section: Group Leader Intentionsmentioning
confidence: 54%
See 2 more Smart Citations
“…Stockton reported that these unique intentions were specifically related to group counseling and working with multiple clients. They also found that intention categories were similar to the already discussed self-talk categories of Hines, Stockton, and Morran (1995), which demonstrated that self-talk and intentions are closely related constructs. This provided strong support that self-talk is involved in the impact of intentions on actual intervention selection.…”
Section: Group Leader Intentionsmentioning
confidence: 54%
“…While both Hines, Stockton, and Morran (1995) and Kivlighan and Quigley (1991) showed that experience level affects group leader selftalk, Hines (1994) did not find the same experience-related differences in cognitive complexity identified by Kivlighan and Quigley. Therefore, Stockton posited that factors other than experience must affect cognitive complexity.…”
Section: Emotional Intensitymentioning
confidence: 74%
See 1 more Smart Citation
“…Two types of thoughts, interpretation of group process and internal question regarding group members, significantly differentiated the experienced group leaders from the less experienced group leaders. Taken together, the Kivlighan and Quigley (1991) and Hines et al (1995) studies show that experienced group practitioners have a more differentiated and complex knowledge structure than do novice group practitioners. Kivlighan, Markin, Stahl, and Salahuddin (2007) examined how novice leaders' knowledge structure of group members changed with group counseling training.…”
mentioning
confidence: 86%
“…There also has been a significant amount of research about case conceptualization in the context of group counseling (Browne, 2005;Christensen & Kline, 2000;Hines, Stockton, & Morran, 1995;Kivlighan, Martin, Stahl, & Salahuddin, 2007;Kivlighan & Quigley, 1991;McPherson & Walton, 1970;Okech & Kline, 2006;Rubel & Kline, 2008). These findings suggest that group counselors' case conceptualizations differ in terms of cognitive organization and complexity (Kivlighan et al, 2007;Kivlighan & Quigley, 1991;McPherson & Walton, 1970), professional experience and feelings of competence (Hines et al, 1995;Okech & Kline, 2006), and thematic content (Browne, 2005;Hines et al, 1995). These studies reveal a significant breadth and depth of information about group counselors' thoughts and perceptions about their groups.…”
Section: Conceptualization In Group Counselingmentioning
confidence: 99%